Mission-Driven Adaptability in a Changing National Training System. Issue 1 (1st December 2016) - Zoellner, Don; Stephens, Anne; Joseph, Victor; Monro, Davena
Abstract : This case study of an adult and community education provider based in far north Queensland describes its capacity to balance various iterations of public policy against its vision for the future of Aboriginal and Torres Straits Islanders. Community-controlled organisations wanting to contribute to economic and social development in regional/remote Australia through the use of formally recognised vocational education and training have adjusted to at least three major sociopolitical changes at the national policy level since the early 1990s. These include redefining equity, marketising the delivery of public services and increased centralisation. The contemporary orientation of vocational education and training as part of the Indigenous Advancement Strategy has become a highly prescriptive and heavily centralised mechanism for the establishment of employment outcomes. This has been framed as an obligation and right of Australian citizenship as opposed to the other wellbeing and personal development benefits of education. This registered training organisation has navigated four burdensome (re)definitions of equity that have made planning and delivery of true lifelong training objectives difficult. The provider has embraced the marketisation of the sector and navigated other policy changes in order to provide the services and knowledge set out in the college mission statement.